ANALISIS PENGENDALIAN INTERN TERHADAP PENJUALAN PADA PT. ARISTA CABANG PANJANG BANDAR LAMPUNG - Nasyaroeka, Jhon; Milyati, Rina (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2011)
Analysis of intern restrain isÂ process to reach one tools to cash sales although credit sales. Without intern restrain very good ,company impossible to success. Sales account system is either analisys intern restrain. sales account system in the company to need cooperation between leader/manajer with white collar worker and sales system. Sales system take hold of actor important.therefore, analysis of intern restrain need to be corporate objective can be achieved.